Alternative Milk Options for Infants with Cow's Milk Allergy: A Systematic Review of Goat's Milk, Plant-Based Milk, and Partially Hydrolyzed Protein - Wija, Ida Bagus Eka Utama; Angelica, Chatrine; Hardiyani, Kartika; Felicia, Mildi; Firmansyah, Gogma; Nandya, Galuh; Tampubolon, Christine Handayani (Rifa'Institute, 2025)
Introduction: Cow's milk allergy (CMA) is the most common food allergy occurring in the first year of life. Restriction of cow's milk and dairy products results in decreased macro- and micronutrient intake, especially in infants who are not breastfed. Therefore, alternative milk supplements for supplemental nutrition in CMA must be considered. Methods: This systematic review used PRISMA guidelines with the PICO search strategy, focusing on RCTs, clinical trials, and observational studies. A comprehensive search was conducted to obtain articles published in English between 2010 and 2025 using ScienceDirect, PubMed, SagePub, and Scopus. Result and Discission: Results A total of 2010 publications were retrieved using relevant search terms. After a rigorous three-stage review, nine studies were selected based on inclusion criteria and deemed suitable for in-depth analysis. These studies addressed tolerance and allergic reactions or cross-reactivity following administration of goat's milk, soy isolate, rice isolate, and partially hydrolyzed formula. Conclusion: In infants with CMA, goat's milk can trigger cross-reactivity. Partially hydrolyzed formulas can be an option for oral food challenges to assess tolerance. Plant-based formulas, particularly rice isolate, are the best choice, especially for those with non-severe CMA and CMA who cannot tolerate extensively hydrolyzed and amino acid-containing formulas.